Determination of the patterns of changes in the quality indicators of crushing corn and sunflower stems by working bodies of technical equipment - Sheichenko, Viktor; Volskyi, Volodymyr; Kotsiubanskyi, Rostyslav; Bonchyk, Vitalii; Shevchuk, Vitaliy; Shevchuk, Misha; Vovk, Viacheslav; Shapoval, Oleksandr (Technology audit and production reserves, 2025)
The object of research is the technological processes of crushing plant residues, corn and sunflower stalks, working bodies of single and double roll crushers, disk harrow, as well as combined unit consisting of disk harrow and single roll crusher. The relevance of the research is due to the need to solve the problem of increasing the efficiency of technological crushing operations by intensifying (increasing) the effects of the working bodies of the tools on the plant environment. A prototype of double roll crusher was developed and manufactured, the cutting knives of which are placed across the entire width of the grip in a staggered manner with the ability to change the angle of inclination to the axis of rotation of the drum in the range of 6–10°. The highest value of the relative frequencies of corn crushing by double roll crusher belonged to the ranges of 51–100 mm and 101–150 mm, the sum of which was 56% and 52%, respectively. The largest share of 48.25% of crushed sunflower stalks by double roll crusher was established for the range of 51–100 mm. The sum of the percentages of crushed sunflower stalks in the ranges less than 50–100 mm was 77.62%, which is 2.36 times more than the similar indicator of single roll crusher, 3 times more than that of a harrow, and almost coincided with the indicators of a combined unit. In a disk harrow, the largest number of shares of crushed corn stalks 42.2% belonged to the range of 151–200 mm, and sunflower stalks 35.2% to the range over 201 mm. In a combined unit, the largest value of the percentage of crushed stalks was established in the range less than 50 mm. For corn, the specified value was 65.4%, for sunflower 41.5%, respectively. The contribution of single roll crusher to the total percentage of crushed stems in the range of up to 150 mm in a combined unit was 44.7% for corn and 47.7% for sunflower. The results of the research are recommended for crop growing systems under the conditions of choosing rational technical and technological solutions for crushing plant residues.